1964
DOI: 10.1002/cjce.5450420504
|View full text |Cite
|
Sign up to set email alerts
|

The pipeline flow of capsules: Part 7 ‐ an experimental investigation of the transport by two oils of single cylindrical and spherical capsules with density equal to that of the oil

Abstract: Critical Reynolds numbers were revealed by the study at which the velocity ratio curves typically achieved minimum or maximum values. The pronounced critical condition at Reynolds number about 1,000 is of particular interest, falling as it does in the middle of the Reynolds number range widely regarded as yielding laminar flow in a long circular pipe, but coinciding with the first manifestations of turbulence reported in previous studies. Velocity ratios for both spherical and cylindrical capsules were found t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

1965
1965
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…During studies of the flow of two immiscible liquids of the same density in transparent pipes, it ,vas observed that slugs of one liquid were carried by the other liqUid (9). The possibility of replacing the slugs of liquid by solid or semi-solid capsules of the same shape became evident at that time, and theoretical and experimental work on this concept has continued at the Research Council's laboratories (1)(2)(3)(4)(5)(6)(7)(8).…”
Section: Test Capsulementioning
confidence: 95%
“…During studies of the flow of two immiscible liquids of the same density in transparent pipes, it ,vas observed that slugs of one liquid were carried by the other liqUid (9). The possibility of replacing the slugs of liquid by solid or semi-solid capsules of the same shape became evident at that time, and theoretical and experimental work on this concept has continued at the Research Council's laboratories (1)(2)(3)(4)(5)(6)(7)(8).…”
Section: Test Capsulementioning
confidence: 95%
“…Figure B sho,..'s the effect on the capsule velocit;J.T of varying the pipe Reynolds number from 100 to 20,000, the capsules being 7-in. cylinders with flat ends and of the same density as tbe liquid (20). Curves for three capsule-diameter to pipe-diameter ratios are presented here to indicate the effect of varying diameter ratios.…”
Section: Velocitiesmentioning
confidence: 98%
“…accepted as representing laminar flow of a liquid in a pipe, the subsequent falling and re-, covery in the transitional region between laminar and turbulent flow, and the instability at Reynolds num-· bers of about 10,000 have been discussed by Ellis' (20). It was suggested tbat there appears to be a series of Re)·nolds numbers at which changes occur in the turbulence of the free stream and which are made manifest by critical regions in the velocity-ratio, Reynolds-number curves of equal-density capsules_ With water at Reynolds numbers between 20,000 and 120,000, a region not shown by tbe Figure, the velocity-ratio curves fan off linearly with the Reynolds number, the negative slope increasing regularly with decrease of capsule diameter, and no further instability is encountered (16).…”
Section: Experimental Apparatus and Pnoceduresmentioning
confidence: 99%
“…Research carried out in the area of hydraulic capsule pipelining has been mostly focused on monitoring the parameters of capsule motion for various types of capsules in horizontal pipelines (Ellis 1964a, b;Ellis and Bolt 1964;Round and Bolt 1965;Ellis and Kruyer 1974;Ellis, Kruyer, and Roehl 1975;Vlasak 1999). Information about capsules behavior in horizontal bend and straight inclined sections of pipe is limited.…”
Section: Introductionmentioning
confidence: 99%